Ultrasonication-based rapid amplification of α-synuclein aggregates in cerebrospinal fluid - Kakuda, Keita (Sci Rep, 2019)
α-Synuclein aggregates, a key hallmark of the pathogenesis of Parkinson’s disease, can be amplified by using their seeding activity, and the evaluation of the seeding activity of cerebrospinal fluid (CSF) is reportedly useful for diagnosis. However, conventional shaking-based assays are time-consuming procedures, and the clinical significance of the diversity of seeding activity among patients remains to be clarified. Previously, we reported a high-throughput ultrasonication-induced amyloid fibrillation assay. Here, we adapted this assay to amplify and detect α-synuclein aggregates from CSF, and investigated the correlation between seeding activity and clinical indicators. We confirmed that this assay could detect α-synuclein aggregates prepared in vitro and also aggregates released from cultured cells. The seeding activity of CSF correlated with the levels of α-synuclein oligomers measured by an enzyme-linked immunosorbent assay. Moreover, the seeding activity of CSF from patients with Parkinson’s disease was higher than that of control patients. Notably, the lag time of patients with Parkinson’s disease was significantly correlated with the MIBG heart-to-mediastinum ratio. These findings showed that our ultrasonication-based assay can rapidly amplify misfolded α-synuclein and can evaluate the seeding activity of CSF.